The philosophical foundation of general education: the development of the intellect - Syed Hussein Alatas (Universiti Kebangsaan Malaysia, 1998)
This article offers some views on the philosophical foundation of general education. General education aims at the education of man from the point of view of his intellectual development that leads to a comprehensive growth of his mind and personality. It is not a mere distribution of disparate knowledge taken from here and there simply to meet the requirement of a degree. It is selecting attention on definite themes in an analytic and intellectual fashion, not covered by professional disciplines, the goals of which, are not to develop a creer but to develop the total personality. It is not the intention to teach a little of everything but to teach enough of certain things.